Diastereodivergent chiral aldehyde catalysis for asymmetric 1,6-conjugated addition and Mannich reactions - Wen, Wei; Luo, Ming-Jing; Yuan, Yi; Liu, Jian-Hua; Wu, Zhu-Lian; Cai, Tian; Wu, Zhao-Wei; Ouyang, Qin; Guo, Qi-Xiang (Nature communications, 2020)
Chiral aldehyde catalysis is a burgeoning strategy for the catalytic asymmetric α-functionalization of aminomethyl compounds. However, the reaction types are limited and to date include no examples of stereodivergent catalysis. In this work, we disclose two chiral aldehyde-catalysed diastereodivergent reactions: a 1,6-conjugate addition of amino acids to para -quinone methides and a bio-inspired Mannich reaction of pyridinylmethanamines and imines. Both the syn - and anti -products of these two reactions can be obtained in moderate to high yields, diastereo- and enantioselectivities. Four potential reaction models produced by DFT calculations are proposed to explain the observed stereoselective control. Our work shows that chiral aldehyde catalysis based on a reversible imine formation principle is applicable for the α-functionalization of both amino acids and aryl methylamines, and holds potential to promote a range of asymmetric transformations diastereoselectively. Chiral aldehyde catalysis is a useful strategy in the catalytic asymmetric α-functionalization of amino methyl compounds but these reaction types are limited. Here, the authors report two chiral aldehyde-catalysed diastereodivergent reactions, namely, a 1,6-conjugate addition and a bio-inspired Mannich reaction.